The value of a nautical chart - Oudet, L. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1973 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Oudet, L. (1973). The value of a nautical chart. The International Hydrographic Review, 50(1), 149–161. https://journals.lib.unb.ca/index.php/ihr/article/view/23844